PENGARUH PENAMBAHAN PENGUSAHA KENA PAJAK, SURAT PEMBERITAHUAN MASA PPN DAN SETORAN PPN (E-Billing) TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI DI KPP PRATAMA SEMARANG TIMUR - Ira Dwi Andriyani, 14.05.52.0088; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
This study aims to determine the effect of variables of adding PKP Terdaftar, letters SPT Per VAT, and Earnings of VAT (E-Billing) on the acceptance of VAT either jointly or partially and to know the variables that have dominant influence. The population in this research is the addition of PKP, Letter of VAT and Earnings Tax (E-billing) registered in Tax Office Pratama East Semarang 2014-2016. The sample of this research is 36 samples with monthly data unit for 3 years with period 2014-2016 registered in KPP Pratama Semarang Timur. This study uses secondary data obtained from KPP Pratama Semarang Timur. The method of analysis used in this study is multiple linear regression. Based on the results of the study can be concluded that the addition of PFM has no effect on VAT acceptance. While Letter of SPT Period and Deposit of VAT (E-Billing) effect on VAT Receipts. Keywords: Taxable Entrepreneur, Notice, E-Billing, Value Added Tax.